Integration of Information for Environmental Security Environmental Security - Information Security - Disaster Forecast and Prevention - Water Resources Management - Coskun, H. Gonca; Cigizoglu, H. Kerem; Maktav, M. Derya (NATO Science for Peace and Security Series C: Environmental Security,, 2008)
In case of security threats there is a need for temporal access to complete, updated, reliable information, in a dedicated form, is an essential prerequisite to effectively counter security threats. Currently the necessary information exists in a multitude of forms and formats geographically and physically scattered over different countries, institutes and organisations, and are subject to widely different data policies and management schemes. Moreover, there is no complete and updated overview of the existing information, e.g. in the form of a metadata catalogue. As a result, integration of this information in case of emergencies has proven to be extremely difficult, if not impossible. Although in some cases, interesting and impressive "demonstrations" have been shown of the possibilities of the integration of information, for a number of reasons these have reached the "operational" stage.